Exploring guests' service experience of boutique backpacker hostels: a critical incident technique (CIT) approach/ Jasmine Zea Raziah Radha Rashid-Radha, Mohd Fadil Mohd Yusof and Noor Azimin Zainol - Rashid-Radha, Jasmine Zea Raziah Radha; Mohd Yusof, Mohd Fadil; Zainol, Noor Azimin (Faculty of Hotel & Tourism Management, Universiti Teknologi MARA, 2022)
This conceptual paper aims to investigate the extent to which current services and facilities provided by boutique hostels influence guests' evaluation of the service experience. The boutique hostel is a fairly new concept that is being introduced to fulfil the expectations of a more heterogenous backpacker market. These hostels have distinct features, such as stylish interior decoration and unique building architecture, that set them apart from the more basic, no-frills hostels. Demands from the more affluent group of backpackers, commonly referred to as flashpackers, have resulted in sophisticated room designs and extra facilities being offered by boutique hostels. Since this is an exploratory research, the Critical Incident Technique (CIT) is being proposed to explore which aspects of their stay are considered memorable in terms of positive experiences. This study is expected to provide an understanding of the different dimensions of the hostel environment that can be enhanced to contribute towards a positive service experience. In terms of managerial implications, findings from this research could provide initial insight into how boutique hostels could be better managed to attract more guests and increase occupancy levels.